2018
DOI: 10.9734/jammr/2018/44904
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ Perception and Practice of Self-medication for Fevers in Under-five Children: A Cross-sectional Study in a Rural Community, South-East Nigeria

Abstract: Background: Self-medication for febrile illnesses in children is a common practice among caregivers particularly in resource limited settings where over-the-counter medications and prescription-only medications are easily accessible. The most often used drugs in these settings include: anti-malaria, analgesics, antibiotics, anti-helminetics local herbs and home-made remedies. The drugs mostly used by caregivers include: Anti-malaria, Local Herbs, Home-made remedies, Analgesics, Antibiotics and anti-helminthics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Given the high risk of misdiagnosis, suboptimal dosages, and adverse drug reactions, self-medication is dangerous, especially in children. 8,11 Our participants' reasons for self-medication were primarily related to their presumed knowledge of the child's illness, underestimating its severity, and minimizing costs, which is consistent with the findings of Muoneke et al 27 who found that presumed experience with treatments, knowledge of previous prescriptions, and dislike of long waiting times in hospitals were the reasons for self-medication among their participants. Nonetheless, poor health-seeking behavior, such as delayed presentation to health facilities and self-treatment at home, is prevalent in our environment.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Given the high risk of misdiagnosis, suboptimal dosages, and adverse drug reactions, self-medication is dangerous, especially in children. 8,11 Our participants' reasons for self-medication were primarily related to their presumed knowledge of the child's illness, underestimating its severity, and minimizing costs, which is consistent with the findings of Muoneke et al 27 who found that presumed experience with treatments, knowledge of previous prescriptions, and dislike of long waiting times in hospitals were the reasons for self-medication among their participants. Nonetheless, poor health-seeking behavior, such as delayed presentation to health facilities and self-treatment at home, is prevalent in our environment.…”
Section: Discussionsupporting
confidence: 88%
“…Nonetheless, poor health-seeking behavior, such as delayed presentation to health facilities and self-treatment at home, is prevalent in our environment. 5,27,29 In our setting, this is a significant contributor to childhood morbidity and mortality. 30,31 Our primary health care system's limited functionality also impedes timely access to health facilities, as does indiscriminate access to prescription drugs in chemist stores, supermarkets, and sometimes from hawkers.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations